Heat dissipation material

By using high-thermal expansion fiber materials with low resin content in the thermally conductive materials of the superconducting type of superconducting wires and forming a high-density fiber entangled structure on the fiber surface, the problems of insufficient heat transfer performance and unstable contact in the prior art are solved, and efficient cooling performance is achieved.

JP7654524B2Active Publication Date: 2025-04-01KURARAY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021178033
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-04-01
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The prior art has problems in the thermally conductive materials of superconducting wires with insufficient heat transfer performance, slow cooling speed and poor thermal stability. Especially in the superconducting cooling type superconducting wires, the contact between the material and the superconducting wire is unstable, affecting the cooling performance.

Method used

A resin with a fiber surface content of less than 5%, the fiber expands a thermally expanded material in the longitudinal direction when cooling, and the sealing property between the fiber and the surface resin is high, and the angle of the fiber in the longitudinal direction is greater than 30 degrees, forming a fiber-entangled part, improving the density and thermal conductivity of the material.

Benefits of technology

It achieves efficient heat transfer performance, ensures stable contact between superconducting wires and thermally conductive materials, and maintains good contact even during cooling, significantly improving cooling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654524000010
    Figure 0007654524000010
  • Figure 0007654524000011
    Figure 0007654524000011
  • Figure 0007654524000001
    Figure 0007654524000001
Patent Text Reader

Abstract

To provide a heat dissipation material which exhibits high heat transferring properties, satisfactorily holds a contact between a superconducting wire rod and a heat dissipation material even in conduction cooling, and exhibits excellent cooling performance.SOLUTION: A heat dissipation material contains a fiber sheet for being arranged between a cooler and a high-temperature superconducting wire rod in a conduction cooling type superconducting coil, wherein an amount of an impregnation resin contained in the fiber sheet is less than 5 mass% on the basis of the total mass of the fiber sheet, heat strain in a fiber direction when at least a part of the fiber forming the fiber sheet is cooled to 77K from 273K is larger than 0, at least a part of the fiber forming the fiber sheet is oriented at an angle larger than 30 degrees relative to the sheet surface, and a percentage of density of the heat dissipation material to density of the fiber forming the fiber sheet is 10% or more and 70% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat sink for placement between a cooling device and a high-temperature superconducting wire in a conduction-cooled superconducting coil. [Background technology]

[0002] The cooling methods for superconducting coils are roughly divided into immersion cooling and conduction cooling. Compared to immersion cooling, conduction cooling has the advantage that it does not require a refrigerant and can be cooled to any temperature. On the other hand, problems such as a slow cooling rate and poor thermal stability have been pointed out.

[0003] For example, Patent Document 1 discloses that a fiber fabric having a dynamic friction coefficient with stainless steel of 0.04 to 0.14 in the temperature range of 280 K to 300 K and a thickness of 0.01 mm to 10 mm is used as an insulating interlayer sheet of the type to be wound between coils in a non-resin-impregnated superconducting coil. However, according to the study by the present inventors, the technology described in Patent Document 1 specifies the dynamic friction coefficient of the fiber fabric against the metal wire relative to stainless steel, so it may not be effective enough for oxide-based superconducting wire or metal-based superconducting wire coated with resin. In addition, since it is premised on use in immersion cooling, in which heat is removed by a coolant flowing through the gaps between the fabric fibers, if the fiber fabric in the same document is used for a conduction-cooled HTS wire, a sufficient cooling effect cannot be obtained.

[0004] Furthermore, glass fiber reinforced composite materials (hereinafter abbreviated as "GFRP") with epoxy resin as the matrix resin are commonly used as coil constituent materials or material for components around the superconducting wire. For example, Patent Document 2 describes a cryogenic spacer made by cutting a fiber reinforced plastic formed by integrally molding inorganic fibers and resin, which has a stress retention rate of 96% or more after 48 hours at 20°C under an initial compressive load of 50 MPa, and a thermal expansion coefficient of 15×10 under no load in the fiber axis direction. -6(1 / °C) or less, and the document describes the production of fiber-reinforced plastics using unidirectional or woven prepreg sheets containing inorganic fibers. However, according to the inventors' investigations, in the technology described in Patent Document 2, GFRP has low thermal conductivity, and because it shrinks when cooled, the adhesion between the superconducting wire and the component made of GFRP decreases, which can lead to a further decrease in thermal conductivity and the generation of frictional heat due to movement of the component.

[0005] In order to solve such problems, Patent Document 3 discloses a heat dissipation material made of fiber-reinforced resin containing 30 to 95 mass % of fibers based on the total mass of the fiber-reinforced resin, the fibers having a tensile strength of 8 cN / dtex or more, a thermal conductivity in the fiber direction at 77 K of 0.20 to 10 W / m K, and a thermal strain in the fiber direction when the heat dissipation material is cooled from 273 K to 77 K of 2500 × 10 -6 ~6500×10 -6 A heat dissipation material with a specific fiber structure has been proposed. This heat dissipation material has specific fibers fixed with resin to ensure shape stability and ease of handling, prevent heat generation due to fiber misalignment, and achieve excellent cooling performance even when cooled. However, there is a constant demand for the development of heat dissipation materials with better heat dissipation properties. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2012-151319 A [Patent Document 2] Japanese Patent Application Publication No. 10-310649 [Patent Document 3] JP 2020-33475 A Summary of the Invention [Problem to be solved by the invention]

[0007] The problem that the present invention aims to solve is to provide a heat dissipation material that exhibits high thermal conductivity, maintains good contact between the superconducting wire and the heat dissipation material even during conduction cooling, and exhibits excellent cooling performance. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention includes the following preferred embodiments. [1] A heat dissipation material comprising a fiber sheet for placement between a cooling device and a high-temperature superconducting wire in a conduction-cooled superconducting coil, the amount of impregnated resin contained in the fiber sheet is less than 5 mass% based on the total mass of the fiber sheet, at least a portion of the fibers forming the fiber sheet have a thermal distortion in the fiber direction greater than 0 when cooled from 273 K to 77 K, at least a portion of the fibers forming the fiber sheet are oriented at an angle of greater than 30 degrees with respect to the sheet surface, and the percentage of the density of the heat dissipation material relative to the density of the fibers forming the fiber sheet is 10% or more and 70% or less. [2] The heat dissipation material according to [1], having one or more entangled fiber parts per 2.4 mm width of any cross section of the heat dissipation material. [3] The heat dissipation material according to [1] or [2], wherein the thermal conductivity of the fibers in the fiber direction at 77 K is 0.20 to 10 W / m·K. [4] The thermal distortion of the fiber in the fiber direction when cooled from 273 K to 77 K is 2500 × 10 -6 ~6500×10 -6 The heat dissipation material according to any one of the above [1] to [3], [5] The heat dissipation material according to any one of [1] to [4] above, wherein the fibers are liquid crystalline polyester fibers. [6] The fiber sheet has a basis weight of 30 to 200 g / m 2 The heat dissipation material according to any one of the above [1] to [5], [7] The heat dissipation material according to any one of [1] to [6] above, wherein the fiber sheet is a continuous nonwoven fabric or a staple fiber nonwoven fabric. [8] The heat dissipation material according to any one of [1] to [7] above, wherein the heat dissipation material has a thickness of 100 to 500 μm. [9] The heat dissipation material according to any one of [1] to [8], wherein 10 or more of the fibers observed within a width of 2.4 mm of any cross section of the heat dissipation material are oriented at an angle of greater than 30 degrees with respect to the sheet surface.

[10] The heat dissipation material according to any one of [1] to [9] above, which does not contain an impregnated resin.

[11] A method for producing a heat dissipation material according to any one of [1] to

[10] above, comprising subjecting a sheet-like fiber aggregate to a hydroentanglement treatment, an airentanglement treatment, a needle punching treatment or a combination of these treatments to form a fiber sheet. Effect of the Invention

[0009] According to the present invention, it is possible to provide a heat dissipation material that exhibits high thermal conductivity, maintains good contact between the superconducting wire and the heat dissipation material even during conduction cooling, and exhibits excellent cooling performance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of an apparatus for measuring the thermal conductivity of a fiber in the fiber direction. [Diagram 2] FIG. 2 is a schematic diagram of an apparatus for measuring the thermal conductivity of a heat dissipation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Heat dissipation material] The heat dissipation material of the present invention is a heat dissipation material comprising a fiber sheet for placement between a cooling device and a high-temperature superconducting wire in a conduction-cooled superconducting coil.

[0012] In the heat dissipating material of the present invention, at least a portion of the fibers forming the fiber sheet are oriented at an angle of more than 30 degrees with respect to the sheet surface, whereby the fibers are entangled with each other to form entangled portions. Furthermore, the percentage of the density of the heat dissipating material relative to the density of the fibers forming the fiber sheet [{(density of the heat dissipating material) / (density of the fibers forming the fiber sheet)}×100] is 10% or more, preferably 15% or more, more preferably 20% or more, and 70% or less, preferably 60% or less, more preferably 50% or less. That is, the heat dissipating material has a certain degree of bulkiness. If the percentage is less than 10%, the number of fibers contributing to heat conduction is small, and sufficient heat transferability may not be obtained. If the percentage is more than 70%, it becomes difficult to orient the fibers in the thickness direction, and when a fiber that expands upon cooling is used, the fiber becomes difficult to expand, and sufficient heat transferability may not be obtained. The percentage can be determined by the method described in the Examples below. When the fiber sheet is formed of multiple types of fibers, the density of the fibers forming the fiber sheet is determined by multiplying the density of each fiber determined by the method described in the Examples below by the ratio of each fiber. For example, when the fiber sheet has a density D 1 40% by mass of fiber 1 having a density D 2 When the fiber 2 is formed of 60 mass % of the fiber 2 having the above structure, the fiber 2 has a thickness of 0.4×D. 1 +0.6×D 2 The density of the fibers forming the fiber sheet is determined by the above.

[0013] The following mechanism of action is presumed to be the reason why the heat dissipating material exhibits high thermal conductivity by combining the above-mentioned characteristics, maintains good contact between the superconducting wire and the heat dissipating material even during conduction cooling, and exhibits excellent cooling performance. First, at least a part of the fibers is oriented at an angle greater than a specific angle with respect to the sheet surface, so that the fibers are entangled (have intertwined parts), ensuring shape stability, and the heat dissipating material is fixed between the cooling device and the superconducting wire by having a specific bulkiness, so that heat generation due to fiber misalignment is unlikely to occur. Then, even during cooling, the entanglement and bulkiness of the fibers act favorably to provide shape stability and resistance to fiber misalignment. In addition, the fibers expand in the orientation direction during cooling, and the adhesion between the heat dissipating material and the superconducting wire and / or the adhesion between the heat dissipating material and the cooling plate of the cooling device increases, so that the heat dissipating material exhibits high thermal conductivity and can exhibit excellent cooling performance even during cooling. However, the above is presumed, and the present invention is not limited to this mechanism of action.

[0014] In the heat dissipation material of the present invention, as described above, shape stability and excellent cooling performance can be achieved even without fixing the fibers with a large amount of impregnated resin. Therefore, the amount of impregnated resin contained in the fiber sheet is less than 5 mass% based on the total mass of the fiber sheet. The amount of impregnated resin contained in the fiber sheet may be 4 mass% or less, 3 mass% or less, 2 mass% or less, or 0 mass% based on the total mass of the fiber sheet. If the amount of resin impregnated in the fiber sheet is smaller, as described below, when a fiber that expands during cooling is used as the fiber forming the fiber sheet, the expansion is less likely to be inhibited, and as a result, the adhesion between the heat dissipation material and the superconducting wire and / or the adhesion between the heat dissipation material and the cooling plate of the cooling device can be improved even during conduction cooling. In a preferred embodiment of the present invention, the heat dissipation material does not contain an impregnated resin.

[0015] The resin to be impregnated into the fibers is not particularly limited. It may be either a thermosetting resin or a thermoplastic resin, and is preferably a thermosetting resin. For example, a soft thermosetting resin such as a urethane-based resin or an acrylic-based resin is more preferable.

[0016] In a preferred embodiment, the heat dissipating material has 1 or more, preferably 2 or more, more preferably 3 or more entangled fiber parts per 2.4 mm width of any cross section of the heat dissipating material. The upper limit of the entangled fiber parts is not particularly limited, and is usually 10 or less. In a preferred embodiment, the heat dissipating material has 10 or more, preferably 50 or more, more preferably 100 or more of the fibers observed within a 2.4 mm width range of any cross section of the heat dissipating material oriented at an angle of more than 30 degrees with respect to the sheet surface. The upper limit of the number of oriented fibers is not particularly limited, and is usually 300 or less. The number of oriented fibers is set to 2, including the bent portion of the continuous fiber. The number of entangled fiber parts and the presence and number of oriented fibers can be evaluated by observing the cross section of the heat dissipation material with a scanning electron microscope, as described in the Examples below. Unlike woven patterns and knitted patterns, entangled fiber parts can be distinguished from each other in images observed with a scanning electron microscope. The presence of one or more entangled fiber parts per 2.4 mm width of any cross section of the heat dissipating material, and the fact that 10 or more of the fibers observed within a 2.4 mm width range of any cross section of the heat dissipating material are oriented at an angle greater than a specific angle, indicate that a certain proportion or more of the fibers are oriented in the thickness direction of the sheet, and that a certain proportion or more of the fibers are entangled with each other. Therefore, in these embodiments, the heat dissipating material exhibits higher heat transfer properties and can exhibit better cooling performance even during cooling. The orientation of the fibers and the formation of the entangled fiber portions can be achieved, for example, by subjecting a sheet-like fiber assembly to a hydroentanglement treatment, an airentanglement treatment, a needle punching treatment, or a combination of these treatments.

[0017] The thickness of the heat dissipating material is preferably 100 μm or more, more preferably 150 μm or more, particularly preferably 200 μm or more, and is preferably 500 μm or less, more preferably 400 μm or less, particularly preferably 300 μm or less. When the thickness of the heat dissipating material is the lower limit or more, it is easy to obtain the desired shape stability and handling, and when the thickness is the upper limit or less, it is easy to obtain the desired heat transferability. The thickness of the heat dissipating material can be measured by the method described in the examples below.

[0018] In addition to the fiber sheet, the heat dissipation material of the present invention may optionally contain some of the components that make up a conduction-cooled superconducting coil, such as a cooling plate, a heat conduction plate and / or a heat conduction wire of a cooling device, as long as the insulation properties are not impaired. From the viewpoint of cooling performance, in one preferred embodiment, the heat dissipation material is made of a fiber sheet.

[0019] In a preferred embodiment, the thermal conductivity of the fibers forming the fiber sheet in the fiber direction at 77K is preferably 0.20 to 10 W / m·K, more preferably 0.25 to 5.0 W / m·K, even more preferably 0.30 to 3.0 W / m·K, and particularly preferably 0.35 to 2.0 W / m·K. When the thermal conductivity is within the above range, the performance as a heat dissipation material is easily exhibited sufficiently. Examples of such fibers include high-strength polyethylene fibers, aramid fibers, and liquid crystal polyester fibers. The fibers forming the fiber sheet may be one type alone or a combination of two or more types. The thermal conductivity can be measured according to the method described in the examples below.

[0020] The friction coefficient of the fibers forming the fiber sheet is preferably in the range of 0.15 to 0.50, more preferably in the range of 0.20 to 0.45. When the friction coefficient is within the above range, the fibers are easily oriented and fiber entanglements are easily formed. Examples of such fibers include aramid fibers and liquid crystalline polyester fibers. The friction coefficient of the fibers can be measured by a radar method with reference to JIS L 1015:2010. For example, the measurement is performed under the conditions of a load of 100 mg and a peripheral speed of 120 rpm, using chromium as the metal.

[0021] At least a portion of the fibers forming the fiber sheet (for example, 30% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more), preferably all of the fibers forming the fiber sheet, have a thermal strain in the fiber direction when cooled from 273 K to 77 K that is greater than 0, preferably greater than 2500 × 10 -6 ~6500×10 -6, more preferably 3000×10 -6 ~6000×10 -6 , and more preferably 3500×10 -6 ~5500×10 -6 In this specification, thermal strain refers to the phenomenon in which a heat dissipating material expands or contracts as the temperature decreases, and if the thermal strain in the fiber direction (fiber axis direction) upon cooling is a positive value, the fibers expand in the fiber direction. In the present invention, since the thermal strain is a positive value, the heat dissipating material exhibits negative expansion characteristics in which the heat dissipating material expands in the fiber direction as the temperature decreases, and excellent cooling performance can be achieved by maintaining good contact between the superconducting wire and the heat dissipating material even during cooling. If the thermal strain is within the above numerical range, it is easy to achieve both thermal strain and good heat transferability, and therefore the performance as a heat dissipating material is easily expressed. Thermal strain can be measured according to the method described in the examples below.

[0022] Examples of fibers having a thermal distortion within the above range include high-strength polyethylene fibers, aramid fibers, and liquid crystalline polyester fibers. Among these, liquid crystalline polyester fibers are preferred because they tend to exhibit a more favorable thermal distortion and because they have a moderate friction coefficient, they are easily oriented when processed into a fiber sheet, and therefore tend to form entangled fiber portions.

[0023] <Liquid crystal polyester fiber> The "liquid crystalline polyester fiber" in the present invention can be produced by melt spinning a liquid crystalline polyester. A liquid crystalline polyester is a polyester that exhibits optical anisotropy (liquid crystallinity) in a molten phase, and can be identified, for example, by placing a sample on a hot stage, heating it under a nitrogen atmosphere, and observing the transmitted light of the sample with a polarizing microscope. The liquid crystalline polyester is composed of repeating structural units derived from, for example, an aromatic diol, an aromatic dicarboxylic acid, or an aromatic hydroxycarboxylic acid, and the structural units are not particularly limited in terms of their chemical structure as long as they do not impair the effects of the present invention. Furthermore, the liquid crystalline polyester may also contain structural units derived from an aromatic diamine, an aromatic hydroxyamine, or an aromatic aminocarboxylic acid, as long as they do not impair the effects of the present invention.

[0024] For example, preferred structural units include the examples shown in Table 1. [Table 1]

[0025] Here, Y is present in a number ranging from 1 to the maximum number that can be substituted in the aromatic ring, and is independently selected from the group consisting of a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), an alkyl group (e.g., an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group, etc.), an alkoxy group (e.g., a methoxy group, an ethoxy group, an isopropoxy group, a n-butoxy group, etc.), an aryl group (e.g., a phenyl group, a naphthyl group, etc.), an aralkyl group [benzyl group (phenylmethyl group), phenethyl group (phenylethyl group), etc.], an aryloxy group (e.g., a phenoxy group, etc.), and an aralkyloxy group (e.g., a benzyloxy group, etc.).

[0026] More preferred structural units include the structural units described in Examples (1) to (18) in Tables 2, 3, and 4. When a structural unit in the formula is a structural unit that can exhibit multiple structures, two or more of such structural units may be combined and used as a structural unit that constitutes a polymer.

[0027] [Table 2]

[0028] [Table 3]

[0029] [Table 4]

[0030] In the constitutional units of Tables 2, 3 and 4, n is an integer of 1 or 2, and each constitutional unit n=1, n=2 may be present alone or in combination; Y 1 and Y 2 may each independently be a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), an alkyl group (e.g., an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group, etc.), an alkoxy group (e.g., a methoxy group, an ethoxy group, an isopropoxy group, a n-butoxy group, etc.), an aryl group (e.g., a phenyl group, a naphthyl group, etc.), an aralkyl group [benzyl group (phenylmethyl group), phenethyl group (phenylethyl group), etc.], an aryloxy group (e.g., a phenoxy group, etc.), an aralkyloxy group (e.g., a benzyloxy group, etc.), etc. Among these, preferred Y is a hydrogen atom, a chlorine atom, a bromine atom, or a methyl group.

[0031] Furthermore, examples of Z include substituents represented by the following formulas. [ka]

[0032] A preferred liquid crystal polyester preferably has two or more kinds of naphthalene skeletons as a structural unit. Particularly preferably, the liquid crystal polyester contains both a structural unit (A) derived from hydroxybenzoic acid and a structural unit (B) derived from hydroxynaphthoic acid. For example, the structural unit (A) may be represented by the following formula (A), and the structural unit (B) may be represented by the following formula (B). From the viewpoint of easily improving melt moldability, the ratio of the structural unit (A) to the structural unit (B) may be preferably in the range of 9 / 1 to 1 / 1, more preferably 7 / 1 to 1 / 1, and even more preferably 5 / 1 to 1 / 1.

[0033] [ka] [ka]

[0034] The total of the structural units (A) and the structural units (B) may be, for example, 65 mol % or more, more preferably 70 mol % or more, and even more preferably 80 mol % or more, based on the total structural units. In particular, liquid crystalline polyesters in which the structural units (B) account for 4 to 45 mol % of the polymer are preferred.

[0035] The melting point of the liquid crystal polyester preferably used in the present invention is preferably 250 to 360°C, more preferably 260 to 320°C. Here, the melting point is the main absorption peak temperature observed when measured by a differential scanning calorimeter (DSC; Mettler's "TA3000") in accordance with the JIS K7121 test method. Specifically, 10 to 20 mg of a sample is taken and sealed in an aluminum pan in the DSC device, and then nitrogen as a carrier gas is passed through at 100 cc / min, and the endothermic peak is measured when the temperature is raised at 20°C / min. If a clear peak does not appear in the first run in the DSC measurement due to the type of polymer, it is preferable to raise the temperature to a temperature 50°C higher than the expected flow temperature at a heating rate of 50°C / min, hold the temperature for 3 minutes, completely melt, and then cool to 50°C at a heating rate of -80°C / min, and then measure the endothermic peak at a heating rate of 20°C / min.

[0036] The liquid crystalline polyester may contain thermoplastic polymers such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefin, polycarbonate, polyamide, polyphenylene sulfide, polyether ether ketone, and fluororesin, within the range that does not impair the effects of the present invention. In addition, various additives such as inorganic substances such as titanium oxide, kaolin, silica, and barium oxide, colorants such as carbon black, dyes, and pigments, antioxidants, ultraviolet absorbers, and light stabilizers may be added.

[0037] The liquid crystalline polyester fiber contained in the heat dissipation material of the present invention can be produced by melt spinning the liquid crystalline polyester by a conventional method. Usually, the liquid crystalline polyester is spun at a temperature 10 to 50°C higher than the melting point of the liquid crystalline polyester. The fiber after spinning may be heat treated. The heat treatment causes solid-phase polymerization (which may also involve a partial crosslinking reaction), improving the strength and elastic modulus, and further increasing the melting point.

[0038] The heat treatment can be carried out in an inert atmosphere such as nitrogen, or in an oxygen-containing active atmosphere such as air, or under reduced pressure. It is preferable to carry out the heat treatment in a gas atmosphere with a dew point of -40°C or less. Preferred temperature conditions include a temperature condition in which the temperature is gradually increased from below the melting point of the liquid crystalline polyester fiber. The heat treatment can be carried out for several seconds to several tens of hours depending on the desired performance. The heat treatment is usually carried out in the form of fiber, but may also be carried out in the form of a nonwoven fabric, woven fabric, knitted fabric, a sheet-like fiber assembly described below, or a fiber sheet, as necessary.

[0039] The single yarn fineness of the liquid crystalline polyester fiber is preferably 0.01 to 50 dtex, more preferably 0.01 to 20 dtex, and particularly preferably 0.01 to 10 dtex. When the single yarn fineness is within the above range, a fiber sheet having a desired thickness and good texture can be easily obtained.

[0040] Commercially available products can also be used as the "liquid crystalline polyester fiber". Examples of such commercially available products include Vectran UM (product name) manufactured by Kuraray Co., Ltd., Vectran HT (product name) manufactured by Kuraray Co., Ltd., Vectran NT (product name) manufactured by Kuraray Co., Ltd., Vectran EX (product name) manufactured by Kuraray Co., Ltd., Sciberas (product name) manufactured by Toray Industries, Inc., and Zexion (product name) manufactured by KB Seiren Co., Ltd. The liquid crystalline polyester fibers can be used alone or in combination.

[0041] [Method of manufacturing heat dissipation material] The heat dissipating material of the present invention can be produced by a production method including subjecting a sheet-like fiber assembly to a hydroentanglement treatment, an airentanglement treatment, a needle punching treatment, or a combination of these treatments to form a fiber sheet. The fibers used to form the fiber assembly are the fibers described above.

[0042] The sheet-like fiber assembly in the present invention means a preliminary nonwoven fabric-like fiber assembly in which the fibers are weakly bonded to each other, or a preliminary fiber assembly in which the fibers are not bonded to each other and have a nonwoven fabric shape in a tangled state. Weak adhesion between fibers can be confirmed, for example, by a weak breaking strength per unit mass or by the occurrence of fluffing when the surface is rubbed with a finger.

[0043] A sheet-like fiber assembly can be obtained, for example, by crimping and cutting the fibers that form the above-mentioned fiber sheet to obtain staples (raw cotton), passing the staples through a card or webber by a known method to obtain a random web or cross-lap web, and laminating these webs.

[0044] The sheet-like fiber aggregate can also be obtained as a nonwoven fabric-like fiber aggregate of the direct spinning type of the resin constituting the fiber forming the fiber sheet. The spinning means is not particularly limited as long as the fiber aggregate can be formed, and for example, the melt blown method, the spunbond method, the electrostatic spinning method, etc. can be adopted. The spinning method may be either melt spinning or solution spinning, but melt spinning is preferred from the viewpoint of controlling the adhesiveness. Among these, the melt blown method is preferred from the viewpoint of excellent production efficiency and the ability to reduce the average fiber diameter. The device used for the melt blown method is not particularly limited, and a conventionally known melt blown device can be used.

[0045] The hole diameter of the spinning nozzle in the meltblown apparatus is preferably 0.1 to 0.5 mmφ, more preferably 0.12 to 0.35 mmφ, from the viewpoint of easily suppressing nozzle clogging or fiber breakage.

[0046] The ratio (L / D) of the nozzle hole length (L) to the nozzle hole diameter (D) of the spinning nozzle in the meltblown machine is preferably 5 to 50, more preferably 8 to 45, from the viewpoints of good productivity and suppression of yarn breakage.

[0047] The distance between the nozzle holes (nozzle hole pitch) is preferably 0.2 to 1.0 mm, and more preferably 0.25 to 0.75 mm. When the nozzle hole pitch is within the above range, fusion between adjacent fibers immediately below spinning is suppressed, which tends to reduce fiber clumps and tends to make the inter-fiber gaps appropriate, making it easier to obtain excellent uniformity in the fiber aggregate.

[0048] In the method of the present invention, the sheet-like fiber assembly described above is subjected to a hydroentanglement treatment, an air entanglement treatment, a needle punching treatment, or a combination of these treatments to form a fiber sheet. From the viewpoint of efficiently obtaining the desired fiber orientation (angle of the fiber relative to the sheet surface, number of oriented fibers), hydroentanglement treatment or needle punching treatment is preferred, and hydroentanglement treatment is more preferred.

[0049] In the case of hydroentanglement, for example, by performing the hydroentanglement process using a nozzle with orifices arranged at specific intervals, some parts of the sheet-like fiber aggregate are particularly hit by the water stream and some parts are relatively not hit by the water stream. Therefore, the number of entangled fiber parts and fiber orientation of the heat dissipating material can be adjusted by adjusting the interval of the orifices. The number of entangled fiber parts and fiber orientation of the heat dissipating material can also be adjusted by, for example, adjusting the moving speed of the sheet-like fiber aggregate or the kinetic energy of the water stream.

[0050] In the case of needle punching, a known felting needle may be used as the felting needle. In order to ensure intertwining in the thickness direction of the sheet-like fiber assembly, a one-barb needle that is less likely to cause fiber breakage is preferably used. In addition, in order to obtain a higher fiber orientation more efficiently, a multi-barb needle such as a three-barb, six-barb, or nine-barb needle may be used. Depending on the purpose, these needles may be combined.

[0051] The number of punches in needle punching varies depending on the shape of the needle used and the thickness of the sheet-like fiber assembly, but is generally 200 to 2500 punches / cm 2 It is set in the range.

[0052] The fiber sheet includes a nonwoven fabric, knitted fabric, or woven fabric bonded to one or both sides of a single nonwoven fabric or nonwoven fabric precursor by hydroentanglement, air current entanglement, or needle punching, and a knitted fabric or woven fabric bonded between two nonwoven fabrics or nonwoven fabric precursors by hydroentanglement, air current entanglement, or needle punching. Here, the nonwoven fabric precursor refers to a sheet-like fiber assembly that forms a nonwoven fabric when subjected to hydroentanglement, air current entanglement, or needle punching. In a preferred embodiment, the fibrous sheet is preferably a nonwoven fabric, more preferably a continuous nonwoven fabric or a staple fiber nonwoven fabric.

[0053] The fiber sheet preferably has a basis weight of 30 to 200 g / m 2 , more preferably 40 to 180 g / m 2 , and more preferably 50 to 160 g / m 2 When the basis weight of the fiber sheet is within the above range, the fiber sheet has a suitable density, and when used as a heat dissipation material, it is easy to obtain excellent heat transfer and insulation properties. The basis weight of the fiber sheet can be measured by the method described in the Examples below.

[0054] As the fiber sheet, a commercially available product may be used, for example, Veclus (product name) manufactured by Kuraray Co., Ltd., which is a liquid crystalline polyester nonwoven fabric. EXAMPLES

[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0056] [Measurement or evaluation method] <Amount of impregnated resin contained in fiber sheet> Mass W of fiber sheet not impregnated with resin 1 The fiber sheet was impregnated with the matrix resin, and the matrix resin was then thermally cured. The mass W of the fiber sheet impregnated with the resin was 2 From these weighed values, the amount of the impregnated resin contained in the fiber sheet was calculated according to the following formula. Amount of impregnated resin = [(W 2 -W 1 ) / W 2 ] x 100

[0057] <Cross-section observation using a scanning electron microscope> The heat dissipation material was cut in the product width direction (CD direction), and the cross section was observed at 100x magnification using a scanning electron microscope. The observed images were evaluated for the following items. At least a portion of the fibers forming the fiber sheet are oriented at an angle of greater than 30 degrees to the sheet surface. -There must be at least one entangled fiber joint forming a fiber sheet per 2.4 mm of cross-sectional width. At least 10 of the fibers constituting the fiber sheet, observed within a cross-sectional area of ​​2.4 mm, are oriented at an angle of more than 30 degrees to the sheet surface. Three cross sections were observed and it was confirmed that the results were the same for all three cross sections.

[0058] <Percentage of density of heat dissipation material relative to density of fibers forming fiber sheet> The density of the fibers forming the fiber sheet was determined by the "density gradient tube method" described in JIS L1015:2010. The density of the heat dissipation material was determined by dividing the basis weight of the heat dissipation material by the thickness. Here, the basis weight of the heat dissipation material was determined according to "mass per unit area" described in JIS L1913:2010, and the thickness of the heat dissipation material was determined according to "Method A" described in JIS L1913:2010. Using these values, the percentage of the density of the heat dissipating material relative to the density of the fibers forming the fiber sheet was calculated according to the following formula. {(density of heat dissipation material) / (density of fibers forming fiber sheet)} x 100

[0059] <Thermal conductivity of the fibers forming the fiber sheet in the fiber direction at 77K> 200 fibers forming the fiber sheet were bundled in one direction and weighed. The fiber bundle was coated with epoxy resin (base: Grade 827 manufactured by Mitsubishi Chemical Corporation, hardener: HN-5500 manufactured by Hitachi Chemical Co., Ltd.) and inserted into a heat-shrinkable tube with a diameter of about 10 mm. After curing the epoxy resin by heating for 2 hours in a dry oven set at 120°C, the heat-shrinkable tube was removed and the fiber was weighed. The amount of epoxy resin was adjusted so that the amount of fiber contained in the resin-impregnated fiber, calculated from these weighing values, was 40 to 55 mass%. Both ends of the fiber-reinforced resin were cut to a length of about 60 mm, and the end faces were trimmed to obtain a test specimen. In the test specimen, the fibers were aligned in one direction and extended between the cut end face and the other end face. The thermal conductivity was measured by the steady heat flow method according to the following procedure using the measuring device shown in Figure 1. Note that in Figure 1 and Figure 2 described later, the dimensions and ratios of each component are appropriately changed to make the drawings easier to understand. (1) A part of the sample (test piece) was inserted into a copper sample stand and fixed to the cold head of the refrigerator. (2) Under vacuum insulation conditions, the sample was cooled to 77 K using a refrigerator. (3) The sample was continuously heated at a constant power (0.03 W) using a heater attached to the top of the sample, creating a steady-state temperature gradient in the sample. (4) The temperature gradient of the sample was measured using two thermocouples. (5) From the measured temperature, the thermal conductivity λ was calculated using the following formula.

number

[0060] <Thermal distortion in the fiber direction of the fiber sheet when cooled from 273K to 77K> A test specimen was prepared in the same manner as the test specimen for measuring thermal conductivity described above, and a strain gauge was attached to measure the thermal strain in the fiber direction of the test specimen. The test specimen was then immersed in ice water to clarify the reference temperature of 273 K. The test specimen was then immersed in liquid nitrogen, and the expansion or contraction when cooled from 273 K to 77 K was measured. Three samples were prepared for each type of fiber, and the expansion or contraction of each sample was measured three times. The average value was taken as the thermal strain in the fiber direction of the fibers forming the fiber sheet when cooled from 273 K to 77 K.

[0061] <Weight of fiber sheet> The basis weight of the fiber sheet was determined in accordance with "mass per unit area" as defined in JIS L1913:2010.

[0062] <Thickness of heat dissipation material> The thickness of the heat dissipation material was determined according to "Method A" described in JIS L1913:2010.

[0063] <Heat transfer properties of heat dissipation materials> The temperature change of the heat dissipating material was measured using the device shown in Figure 2. Forty layers of plate-shaped YBCO wires (yttrium-based high-temperature superconducting wires) were arranged vertically, and Hastelloy wires were inserted between the 20th and 21st layers of YBCO wires as heaters. Next, thermocouples TC1, TC2, and TC3 were inserted between the 0-1, 7-8, and 14-15th layers of YBCO wires from the Hastelloy wires, respectively, to create a wire pack. The wire pack was sandwiched between copper blocks on both sides, and pressure was applied to a surface pressure of 1.4 MPa. The heat sink was cut to have the same area as the bottom area of ​​the wire pack, and the wire pack was stacked from the bottom to form a wire pack sandwiched between a copper block, a heat sink (labeled "test sample" in Figure 2), and a copper block, and a GFRP block was used to apply a surface pressure of 1.4 MPa to the top of the wire pack. This was placed in a refrigerator, the inside of which was evacuated, and cooled to a set temperature of 77 K. After the temperatures measured by the three thermocouples became constant, heat was input with a heater output of 300 mW, and the temperature change ΔT at each thermocouple after 5,000 seconds, when it became roughly constant, was evaluated as thermal conductivity. The smaller ΔT indicates better thermal conductivity. In FIG. 2, in order to make the drawing easier to understand, the wiring from the Hastelloy wire to the power supply and the wiring from each thermocouple to the amplifier are omitted.

[0064] Example 1 A liquid crystalline polyester (Laperos A type, manufactured by Polyplastics Co., Ltd.) consisting mainly of parahydroxybenzoic acid and 6-hydroxy-2-naphthoic acid was used to obtain a liquid crystalline polyester multifilament 1 (hereinafter abbreviated as "filament 1") having a total fineness of 1670 dtex and 600 filaments. The coefficient of friction of filament 1, measured by the radar method with reference to JIS L 1015:2010, was 0.26. The thermal conductivity and thermal distortion of filament 1 were measured. The results are shown in Table 5. Filament 1 was crimped and cut to obtain raw cotton with a single yarn fineness of 2.8 dtex and a fiber length of 38 mm. This raw cotton was used to prepare a semi-random web by the carding method, which was placed on a punching drum support with a hole diameter of 0.3 mm and continuously transported. At the same time, a high-pressure water flow was sprayed from above to perform an entanglement process, thereby obtaining a resin sheet (short fiber nonwoven fabric). This resin sheet was used as a heat dissipation material, and various measurements and evaluations were carried out. The results are shown in Table 5.

[0065] Example 2 A nonwoven fabric precursor was produced by the melt-blown method using a liquid crystal polyester (Laperos L type, manufactured by Polyplastics Co., Ltd.) consisting mainly of parahydroxybenzoic acid and 6-hydroxy-2-naphthoic acid. A part of the obtained nonwoven fabric precursor was unraveled and aligned to obtain a bundle (tow) of liquid crystal polyester fibers having an average fiber diameter of about 3 μm (hereinafter abbreviated as "tow 1"). The friction coefficient of tow 1, measured by the radar method with reference to JIS L 1015:2010, was 0.30. The thermal conductivity and thermal distortion of tow 1 were measured. The results are shown in Table 5. The nonwoven fabric precursor was prepared in a portion other than the nonwoven fabric precursor taken out of the tow 1 for measuring the thermal conductivity and thermal distortion, and was subjected to a high-pressure water flow entanglement treatment in the same manner as in Example 1 to obtain a resin sheet (continuous nonwoven fabric). This resin sheet was used as a heat dissipation material, and various measurements and evaluations were carried out. The results are shown in Table 5.

[0066] Comparative Example 1 A GFRP sheet (Risho Kogyo, ES-3230J, thickness 0.2 mm) made of glass cloth and epoxy resin was used as a heat dissipation material, and various measurements and evaluations were carried out. In addition, the thermal conductivity and thermal distortion of the glass fiber corresponding to the glass fiber that constitutes the glass cloth contained in the GFRP sheet were measured. The results are shown in Table 5.

[0067] Comparative Example 2 The thermal conductivity and thermal distortion of liquid crystalline polyester fiber Vectran HT (manufactured by Kuraray Co., Ltd., fineness 220 dtex) were measured. The results are shown in Table 5. A woven fabric with a thickness of 200 μm was produced using Vectran HT, with a weave density of 55 threads / inch in the warp direction and 55 threads / inch in the weft direction. This fabric was impregnated with epoxy resin (base: Grade 827 manufactured by Mitsubishi Chemical Corporation, hardener: HN-5500 manufactured by Hitachi Chemical Co., Ltd.) and heated at 120°C for 2 hours to obtain a fiber-reinforced resin sheet. This fiber-reinforced resin sheet was used as a heat dissipation material, and various measurements and evaluations were carried out. The results are shown in Table 5.

[0068] Reference example 1 Toyobo Dyneema® SK60 is cut to 38 mm and carded to a weight of 70 g / m 2 A nonwoven fabric precursor was obtained and subjected to a high-pressure hydroentanglement treatment in the same manner as in Example 1. Although a carded web having a thickness of about 200 μm was obtained with poor texture, the fibers were not sufficiently entangled even after the high-pressure hydroentanglement treatment, possibly due to the low friction coefficient of the fibers (friction coefficient measured by the radar method with reference to JIS L 1015:2010: about 0.1), and a nonwoven fabric could not be produced.

[0069] [Table 5]

[0070] As can be seen from Table 5, all of the heat dissipation materials according to the present invention showed high thermal conductivity. This is believed to be because at least some of the fibers were oriented at an angle greater than a specific angle with respect to the sheet surface, which caused the fibers to become more entangled with each other, and because the heat dissipation material had a specific bulkiness, it was fixed between the cooled copper block and the superconducting wire, making it difficult for heat generation due to fiber misalignment to occur. In addition, the fibers, which have high thermal conductivity at 77K, expanded in the fiber direction upon cooling, and this expansion was not inhibited by the impregnating resin, which is believed to have further improved the adhesion between the heat dissipation material and the superconducting wire and between the heat dissipation material and the copper block, resulting in further improvement in cooling performance.

[0071] On the other hand, in Comparative Example 1, where a GFRP sheet was used as the heat dissipation material, the thermal conductivity was significantly low. This is thought to be due to the fact that at least some of the fibers were not oriented at an angle greater than a specific angle relative to the sheet surface, the entire heat dissipation material, including the fiber direction, contracted during cooling, and the glass fiber itself had a low thermal conductivity at 77K. Although the fibers in the fiber sheet have high thermal conductivity at 77 K, in Comparative Example 2, in which the fiber sheet contains 5 mass % or more of impregnated resin and no fibers are oriented at an angle of more than 30 degrees to the sheet surface, the thermal conductivity was low. One reason for this is thought to be that the expansion of the fibers during cooling did not effectively improve the adhesion between the heat sink and the superconducting wire, and between the heat sink and the copper block. [Industrial Applicability]

[0072] The heat dissipation material of the present invention exhibits high thermal conductivity and exhibits excellent cooling performance even during cooling, and therefore can be suitably used as a heat dissipation material in particular for conduction-cooled HTS coils. [Explanation of symbols]

[0073] 1 Heater 2 Thermocouple 1 3 Thermocouple 2 4. Samples 5 Sample stage 6. Cold Head

Claims

1. A heat dissipation material comprising a fiber sheet for placement between a cooling device and a high-temperature superconducting wire in a conduction-cooled superconducting coil, wherein the amount of impregnated resin contained in the fiber sheet is less than 5 mass% based on the total mass of the fiber sheet, at least a portion of the fibers forming the fiber sheet have a thermal distortion in the fiber direction that is greater than 0 when cooled from 273 K to 77 K, at least a portion of the fibers forming the fiber sheet are oriented at an angle of greater than 30 degrees with respect to the sheet surface, and the density of the heat dissipation material relative to the density of the fibers forming the fiber sheet is 10% or more and 70% or less.

2. The heat dissipation material according to claim 1, having one or more intertwined fiber portions per 2.4 mm width of any cross-section of the heat dissipation material.

3. The heat dissipation material according to claim 1 or 2, wherein the thermal conductivity of the fibers in the fiber direction at 77K is 0.20 to 10 W / m·K.

4. The thermal distortion of the fiber in the fiber direction when cooled from 273 K to 77 K is 2500 × 10 -6 ~6500 x 10 -6 The heat dissipation material according to any one of claims 1 to 3.

5. The heat dissipation material according to any one of claims 1 to 4, wherein the fibers are liquid crystalline polyester fibers.

6. The fiber sheet has a basis weight of 30 to 200 g / m 2 The heat dissipation material according to any one of claims 1 to 5.

7. The heat dissipation material according to any one of claims 1 to 6, wherein the fiber sheet is a continuous nonwoven fabric or a staple fiber nonwoven fabric.

8. The heat dissipation material according to any one of claims 1 to 7, wherein the heat dissipation material has a thickness of 100 to 500 µm.

9. The heat dissipation material according to any one of claims 1 to 8, wherein 10 or more of the fibers observed within a width of 2.4 mm of any cross section of the heat dissipation material are oriented at an angle of more than 30 degrees with respect to the sheet surface.

10. The heat dissipation material according to any one of claims 1 to 9, wherein the heat dissipation material does not include an impregnated resin.

11. The method for producing a heat dissipation material according to any one of claims 1 to 10, comprising subjecting a sheet-like fiber aggregate to a hydroentanglement treatment, an airentanglement treatment, a needle punching treatment, or a combination thereof to form a fiber sheet.

Citation Information

Patent Citations

  • Cryogenic device

    JP1992266077A

  • Superconductive magnet device

    JP1994244027A

  • Superconducting coil

    JP1996115813A

  • Cryogenic spacer and production thereof

    JP1998310649A

  • Superconducting coil

    JP2012151319A